Analisis Pendapatan Asli Daerah dan Penanaman Modal dalam Negeri terhadap Indeks Pembangunan Manusia dengan Tingkat Kemiskinan sebagai Variabel Intervening pada Provinsi Jawa Timur - Ninda Talita Utami; Niniek Imaningsih (Journal of Management and Bussines (JOMB), 2024)
This research aims to evaluate the impact of Regional Original Income (PAD) and Domestic Investment (PMDN) on the Human Development Index (HDI) in East Java province during the 2007-2021 period, with poverty as an intermediate variable or intervening variable. A quantitative approach is applied using multiple linear regression techniques and path analysis as the main methods. The research results show that there is a direct positive and significant relationship between PAD, PMDN, and HDI. However, through path analysis, there is no indication of an indirect influence through poverty on HDI from PAD and PMDN. The implications of these findings can provide a deeper insight into regional development strategies, by highlighting the importance of increasing PAD and PMDN directly to support increasing HDI. In conclusion, the results of this research contribute to understanding the dynamics of the interaction of economic and social variables in the context of regional development in the province of East Java. Keywords: Human Development Index, Regional Original Income, Domestic Investment, Poverty Level